Efforts on Small- and Large-Scale Cultivation of Isochrysis galbana for Enhanced Growth and Lipid Production: A Systematic Review Towards Biorefinery Applications - Meneses-Montero, Karla; Rojas-Villalta, Dorian; Orozco-Ortiz, Cristofer; Jerez-Navarro, Alexis; Gómez-Espinoza, Olman (Bioenergy research, 2025)
Isochrysis galbana is a subject of study for its potential application across different biorefinery industries, due to its biological and biochemical characteristics. However, the optimization of culture conditions and assessment of current efforts towards the scaling from laboratory to small to large scale are pertinent to be addressed. The review aims to summarize the research related to the culture of I. galbana , focusing on identifying the optimal parameters that improve growth and lipid production. In addition, small- and large-scale cultures and downstream processes are explored. Optimal culture conditions include growth on F/2 or Walne media, use of additives (e.g., fertilizer, iron), 400 µmol m −2 s −1 irradiance, 18:6-h light:dark photoperiod, 30 °C temperature, 30–35 psu salinity, 7.5–8.5 pH, and 1.5% CO 2 -enrich airflow. Meanwhile, only a few studies have cultured I. galbana in small- and large-scale systems. Small-scale production results highlight the relevance of parameter optimization, as productivities vary across studies. Moreover, large-scale systems revealed high biomass and lipid productivity. Downstream processing of this microalgal biomass is evaluated, and centrifugation, − 80 °C storage, enzyme inactivation, and Folch extraction methods are the preferred protocols. Overall, the application of novel genetic modification strategies holds promises for enhancing growth and lipid accumulation . Isochrysis galbana represents a relevant species for biorefinery industries; the culture under optimized conditions and suitable systems could greatly enhance its viability. However, forthcoming research in genetically engineered strains and study of the intra-strain variations of this species are required to completely assess its biotechnological potential.